Implementation of Performance Management at CV Nuansa Color Tanjung Pinang Branch - Amelia Amelia; Halimah Sulanjari; Rezi Anggaraini; Sellina Sellina; Satriadi Satriadi (International Forum of Researchers and Lecturers, 2025)
This study aims to analyze and describe the implementation of performance management at CV Nuansa Warna Tanjungpinang Branch. The type of research used is descriptive research with a qualitative approach. Data collection techniques are carried out through observation and in-depth interviews. The sample used in this research is a purposive sample with the informant, SPV, Mr. Riyanto Setiyawan . Data analysis was carried out using triangulation through the steps of reduction, presentation and conclusion. The results of this study found that the implementation of performance at CV Nuansa Warna Tanjungpinang Branch has been implemented quite well. This includes the stages of planning, monitoring, evaluation, and follow-up. However, there are some obstacles, such as CV Nuansa Warna facing unique challenges in implementing performance management, including limited resources, and structured formal systems. Implemented strategies include technical training, KPI implementation, and CRM system development. This study concludes that effective performance management can improve productivity, service quality, and competitiveness of the company, although it requires continuous improvement to face the existing challenges.